Navigating Pastoral Grief: An Analysis of I Thessalonians 4:13 and Pixar's Coco (Institut Agama Kristen Negeri Manado, 2025)
A wise sentence states that fear cannot stop death, but rather stops life. Through this wise sentence, it can be learned that fear of death is actually useless and can even cause harm. This applies to all forms of death, including the death of a loved one. In theology, there is a term known as Pastoral Grief which seems to be the branch of theology that deals most with grief that arises due to death. Pastoral Grief's efforts to overcome grief become increasingly difficult when many parties put forward the concept of